2021
DOI: 10.2478/jtim-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of digestive endoscopic results during COVID-19

Abstract: ObjectiveThis study aims to explore the necessity and safety of digestive endoscopy during the epidemic of coronavirus disease 2019.MethodsA retrospective cohort study method was used to collect patients’ data from the endoscopy center of the Civil Aviation General Hospital of China from February 1 to May 31, 2020, as the observation group. The patients’ data of endoscopic diagnosis and treatment during the same period in 2019 were used as a control group, to compare the differences in the number of diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
0
18
0
6
Order By: Relevance
“…There is a linear model relationship between the number of endoscopies and gastric cancer [ 18 ]. The number of endoscopies decreased during the COVID-19 epidemic, but the rate of diagnosis increased significantly [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a linear model relationship between the number of endoscopies and gastric cancer [ 18 ]. The number of endoscopies decreased during the COVID-19 epidemic, but the rate of diagnosis increased significantly [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…During corona virus limitations, the diagnosis of cancer has been significantly reduced. But after lifting the restrictions, the endoscopy performance returned to normal The endoscopies were postponed or canceled Lui [ 18 ] China A population-based study Good The average number of stomach cancers diagnosed each week decreased by 46.2% The results of linear regression model showed that there is a relationship between the number of gastric cancers and endoscopy performing Huang [ 16 ] China A retrospective cohort study Good Endoscopy decreased by 30.63% during the epidemic compared to the same period last year. The rate of gastric cancer diagnosed has increased in endoscopies Armellini [ 28 ] Italy Retrospectively analyzed endoscopies Good In the study of 847 patients from 13 centers in Italy for endoscopy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations